Faktor Lingkungan Dan Kejadian Diare Pada Balita Di Puskesmas Darussalam - Asnita Yani; Tifani Hadi Tri Wahyuni (STIKES Columbia Asia Medan, 2025)
Background: Diarrhea remains one of the leading causes of morbidity and mortality among children under five in Indonesia. Household environmental conditions, such as water quality, latrine sanitation, waste management, and environmental cleanliness, are important risk factors influencing the incidence of diarrhea. Darussalam Health Center is one of the working areas with a relatively high number of diarrhea cases among children under five. Objective: This study aims to analyze the relationship between environmental factors and the incidence of diarrhea among children under five in the working area of Darussalam Health Center. Methods: This study employed an observational analytic design with a cross-sectional approach. A total of 120 children under five were selected using purposive sampling based on inclusion criteria. Data were collected through interviews using a structured questionnaire and observation of household environmental conditions. Data analysis was performed using the chi-square test and logistic regression. Results: The incidence of diarrhea among children under five was 32.5%. Environmental factors significantly associated with diarrhea were water quality (p = 0.001; OR = 3.98; 95% CI = 1.82–8.71), latrine sanitation (p = 0.004; OR = 3.21; 95% CI = 1.45–7.09), and waste management (p = 0.012; OR = 2.54; 95% CI = 1.22–5.28). Lighting and home ventilation factors were not significantly related. Conclusion: Environmental factors, particularly water quality, sanitation, and waste management, are strongly associated with the incidence of diarrhea among children under five in the working area of Darussalam Health Center.